A Rare Case Report of Colonic Pseudolipomatosis with Distinct Endoscopic and Histological Features - Qi Zhao; Hai-Tao Yu; Qun-Ying Wang; Wei Zhang; Wen-Zhu Dong (Case Reports in Gastroenterology)
Introduction: Colonic pseudolipomatosis is a rare benign lesion with distinct endoscopic and histological features. The etiology and pathogenesis of colonic pseudolipomatosis have not been fully clarified and are still controversial to some extent. It is particularly noteworthy that this lesion must be differentiated from real pathological entities to avoid further unnecessary auxiliary examinations and overtreatments. Case Presentation: We report a case of a 61-year-old woman who underwent regular postoperative follow-ups of rectal cancer. The colonoscopy showed multiple slightly elevated whitish plaques with irregular shapes in almost all of the colon. The plaques were biopsied to further define the focal nature. Further histopathological examination revealed numerous scattered or clustered adipocyte-like vacuoles in lamina propria. Immunohistochemistry results were negative for anti-CD34 and anti-protein S-100, supporting the diagnosis of pseudolipomatosis. Conclusion: Colonic pseudolipomatosis is a rare and benign self-limiting condition that should not be mistaken for a pathological entity, especially active inflammation or malignant tumor. Endoscopic lesions commonly regress spontaneously without complications and appropriate management is necessary because it requires no further investigations or treatments.